1987
DOI: 10.1159/000184546
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and Primary Hypertension

Abstract: The role of dietary calcium in essential hypertension remains controversial. Various studies have found on the one hand a weak negative correlation between blood pressure and Ca2+ intake in special groups, and on the other hand a positive correlation between serum Ca2+ concentration and blood pressure. Several disturbances of cellular Ca2+ metabolism have been described in essential hypertension and in the spontaneously hypertensive rat. Possibly the elevation of intracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Our finding of a positive association between elevated serum total calcium levels and hypertension is consistent with several previous studies 1,6–34 . Jorde and colleagues, in a large cross‐sectional study of 12,865 men and 14,293 women in Norway, reported that serum total calcium was positively associated with hypertension in both men and women after adjusting for age, BMI, heart rate, and cholesterol 6 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding of a positive association between elevated serum total calcium levels and hypertension is consistent with several previous studies 1,6–34 . Jorde and colleagues, in a large cross‐sectional study of 12,865 men and 14,293 women in Norway, reported that serum total calcium was positively associated with hypertension in both men and women after adjusting for age, BMI, heart rate, and cholesterol 6 .…”
Section: Discussionsupporting
confidence: 92%
“…An association between serum total calcium and hypertension is plausible, including a direct effect on vasculature by enhanced vascular resistance, 19 alteration in extracellular binding of calcium, 20 interaction between serum calcium, and other cations such as sodium, potassium and magnesium, 21 renal vasoconstriction causing kidney dysfunction, 22 and hyperactivity of renin‐angiotensin system from hyperparathyroidism 23 . Animal studies have demonstrated elevated total calcium concentrations but normal ionized calcium levels in spontaneously hypertensive rats 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Serum calcium may directly affect vasoconstriction by the influx of calcium into the smooth muscle of the artery, which enhances muscle contracture, increases vascular resistance, and therefore, leads to the development of hypertension ( 43 ). Additionally, calcium could indirectly promote hypertension by alteration in the extracellular binding of calcium ( 44 ), inducing insulin resistance ( 38 ), and interacting with other cations, especially sodium and potassium ( 45 ). Another possible mechanism lies in that subtle alterations in intracellular calcium may affect the secretion and action of hormones, such as the pressor action of catecholamines, angiotensin II, or aldosterone, which may target the blood pressure control centers and increase blood pressure levels ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular calcium level may influence intracellular calcium level and possibly play a role in the pathogenesis of essential HTN (41). The biological mechanisms underlie serum total calcium and blood pressure maybe attribute to a direct effect on vascular by enhanced vascular resistance (42), interaction between serum calcium and other cations (43), alteration in extracellular binding of calcium (44), renal vasoconstriction causing kidney dysfunction (45), and hyperactivity of renin-angiotensin system from hyperparathyroidism (46). Emerging studies have been focused on the role of serum calcium to blood pressure.…”
Section: Discussionmentioning
confidence: 99%